2015
DOI: 10.1146/annurev-immunol-032414-112043
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Recognition of Cancer

Abstract: The observation that a subset of cancer patients show evidence for spontaneous CD8+ T cell priming against tumor-associated antigens has generated renewed interest in the innate immune pathways that might serve as a bridge to an adaptive immune response to tumors. Manipulation of this endogenous T cell response with therapeutic intent-for example, using blocking antibodies inhibiting PD-1/PD-L1 (programmed death-1/programmed death ligand 1) interactions-is showing impressive clinical results. As such, understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
366
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(372 citation statements)
references
References 267 publications
(291 reference statements)
4
366
0
2
Order By: Relevance
“…The presence of spontaneous TILs correlates with better prognosis, especially for tumor immunotherapies (Woo et al, 2015). Recently, consistent with our observations, two exceptional studies have shown that both mouse and human tumor cells can program to suppress chemokine productions that can limit immune infiltrates leading to resistance to Tang et al Page 9 Cancer Cell.…”
Section: Discussionsupporting
confidence: 83%
“…The presence of spontaneous TILs correlates with better prognosis, especially for tumor immunotherapies (Woo et al, 2015). Recently, consistent with our observations, two exceptional studies have shown that both mouse and human tumor cells can program to suppress chemokine productions that can limit immune infiltrates leading to resistance to Tang et al Page 9 Cancer Cell.…”
Section: Discussionsupporting
confidence: 83%
“…The adjuvant directs the DC-priming host immune system to respond to the appropriate target: generating mature DC for tumor eradication. 9 We show in this report that a TLR3-specific adjuvant preferentially induces TAA-specific CTL as well as NK cell activation without provoking inflammation or systemic cytokinemia. 8 Immunotherapy with antibodies against PD-L1 or PD-1 has brought cancer patients hope of a positive outcome: in patients with an inoperable solid tumor, more than 20% diminished without severe side-effects.…”
Section: Immunotherapy Perspectivesmentioning
confidence: 54%
“…EG7 (OVA), B16 (survivin) and C1498 (WT1) were found to be good systems in C57BL/6 mice, and we mainly used the EG7 (OVA)-implant system, since OVA is a multi-epitope antigen and CTL activation is represented by SL8-tetramer. 8,9 OT-1 proliferation, tetramer assay and IFNg production were employed to measure CTL production. Therapeutic response was monitored by tumor shrinkage, and parallelism was checked by monitoring cytokine levels in serum, NK cell and TAA-specific CTL activation.…”
Section: Development Of a Tlr3-defined Adjuvantmentioning
confidence: 99%
“…Nonetheless, there has been growing awareness over the last decade that innate immune responses, including those mediated by NK cells, play a major role in immunosurveillance against some tumor types, especially at the level of metastatic dissemination. 1 This chronological sequence (T before NK cells) most likely does not indicate a hierarchy of importance between T and NK lymphocytes, but rather reflects three interrelated facts, namely, (i) a relatively poor knowledge on the physiology of NK cells (as compared to T lymphocytes), (ii) the existence of major species differences between mouse and human NK cells, and (iii) the absence of standardized tools for the functional exploration of human NK cells. 2 On theoretical grounds, anticancer immunosurveillance may occur in two specific situations.…”
mentioning
confidence: 99%